Feasibility of electro-reduction of U(VI) in oxalic acid using an electrolytic CEM-separated cell - Potgieter, M.; van der Spoel Badenhorst, W. D.; Barry, J. C.; van der Westhuizen, D. J.; Krieg, H. M. (Journal of radioanalytical and nuclear chemistry, 2020)
The feasibility of electrolytic stripping of U(VI) using an electrolytic separation cell with anode and cathode compartments, separated by a cation exchange membrane (CEM), was investigated as a possible final step in a traditional solvent extraction process to recover uranium. The reduction mechanism of U(VI)–U(IV) in oxalic acid was compared with the well-known nitric acid and hydrazine mechanism. It was shown that a similar mechanism was followed in both electrolytes, forming a U(V) intermediate followed by disproportionation to U(IV) and U(VI). Measurable amounts of U(IV) were produced and the transfer of U(VI) through the CEM with simultaneous electro-reduction to U(IV) was confirmed.